Association between Metabolic Syndrome Criteria and Lifestyle Category among University Academic Staff in West Java, Indonesia - Tarawan, Vita Murniati; Fatimah, Siti Nur; Nurhayati, Titing; Akbar, Mohammad Rizki; Radhiyanti, Putri Teesa; Purba, Ambrosius; Akbar, Ieva Baniasih; Goenawan, Hanna (Pakistan Journal of Nutrition, 2018)
Background and Objective: Metabolic syndrome (MetS) prevalence is rising globally, especially in the higher educational community, such as university academic staff. The MetS risk factor is unbalanced nutritional intake combined with insufficient physical activity. Therefore, our goal is to examine the effects of gender, age, nutrient intake and physical activity on hypertension, central obesity and hypertriglyceridemia probability as an important component of MetS among university academic staff. Methodology: The method of this study was a cross-sectional survey and physical examination of MetS on 210 academic staff from Universitas Padjadjaran, Bandung, Indonesia, in 2017. Body height was measured with a stadiometer. Nutritional status and fat mass were measured with a Tanita Bioimpedance Analyzer (BIA). The nutrition intake analysis applied a repeated 24 h food recall method. Physical activity was assessed using the Young Men’ Christian Association (YMCA) step test and Global Physical Activity Questionnaire (GPAQ). Triglyceride level was evaluated by the glycerol-3-phosphate oxidase-phenol aminophenazone (GPO-PAP) method. The data were analyzed with chi-square or Fisher’ exact test and a logistic regression test. Results: Analysis findings showed a significant association between gender, age and nutritional status, with 72% probability of hypertension; a significant relationship among gender, age, nutritional status, fat mass and physical fitness, with 98% probability of central obesity; and an association among gender, age and physical fitness, with 4.9% probability of hypertriglyceridemia. Conclusion: These results suggest that middle-aged males who are more than 35 years old, combined with over-nutritional status, less dietary intake, less physical activity and low physical fitness have a higher risk of developing MetS.